Clinical features, diagnosis, and types of optic neuritis - Hanafi, Hany Abdelmoneim; Alghamdi, Hanin Abdullah; Bassir, Samir Sulaiman; Almutairi, Salman Mubarak; Albalawi, Athari Za’al; Aljaber, Sara Adnan; Alyousif, Abrar Abdullah; Almuraydhi, Khaled Mohammed; Alsamadani, Jumana Hamid; Aljadrawi, Razan Ahmed; Matuk, Fatemah Khawyter; Alsubaie, Maha Fawaz; et al. (International Journal Of Community Medicine And Public Health, 2021)
Establishing a proper diagnosis and identifying the underlying etiology of optic neuritis can be challenging in clinical settings. This is due to the various subtypes and etiologies that were reported for the condition. However, conducting a thorough examination and the laboratory and imaging modalities can significantly enhance the diagnosis. Therefore, it is essential to be adequately aware of the different subtypes of optic neuritis and distinguish between the different clinical features and diagnostic findings of each subtype to conduct a proper diagnosis and enhance management of the affected cases. Optic neuritis is a severe condition that can lead to permanent vision loss. In the present literature review, we have discussed the potential clinical features and diagnostic findings of the different types of optic neuritis. More severe cases of optic neuritis are usually associated with NMOSD and IgG-MOG cases with a worsened prognosis. Painless and chronic vision loss might occur secondary to infections and granulomatous diseases. On the other hand, optic neuritis secondary to multiple sclerosis is usually self-limited. Many of the cases of optic neuritis are characterized by being responsive to steroid therapy. However, acute vision loss was also reported in some cases. Therefore, clinicians must be knowledgeable enough to conduct the most appropriate diagnostic and management modalities to enhance the prognosis of the affected patients. Further research is needed for optimizing the treatment plan and drawing better interventions.